Desarrollo e implementación de un aplicativo web de comercio electrónico para la gestión de ventas de productos del hogar en el almacén Carlitos del cantón La Maná. - Pilaguano Patango, Rafael Efraín (2022)
This research project implemented an e-commerce web application for the management of sales of household products in the Carlitos store in La Maná canton. The application of research techniques allowed us to collect information, design, and create the web system through the application of instruments and types of research such as applied or field. As a result, obtaining the acquisition of requirements indispensable for the development of the software with the high-level programming language, the database management system, and the agile methodology Scrum with its interactive incremental module in the development of this project clears the way for the creation of server-side working models, as well as the views of the software used in companies for digital transformation. The e-commerce system that has been implemented with the hypertext preprocessor programming language and data storage will allow the web application to have the functionality to monitor the company's products, make the orders when the user is properly registered, and on other hand the administrator will provide support, to register new products, the processes performed are validated by users and are configured the web application according to the standardization of Carlitos store.